Sustainable Development and Renewable Energy Policies in the European Union: Transformations and Impacts - CIOBANU, Ghenadie; Cristian VASILACHE, Petruț; Roxana COSMA, Maria; Maria CALIN, Ana (European Journal of Sustainable Development, 2024)
The development of renewable energies in the EU is essential for sustainable development and energy security, having a significant impact on labor markets. Strategies and policies target the EU's objectives and commitments, financial incentives, regulations, innovations, research, in line with labor market opportunities. Reconversion of the workforce and transition to renewable energies are needed, as well as reskilling from traditional industries to green energy sectors. and reducing dependence on fossil energy sources contributes to energy security in the EU. Our proposals emphasize the importance of renewable energies in the reduction of greenhouse gas emissions and the preservation of the environment, with a particular emphasis on the promotion of sustainable development. Ensuring energy security and sustainable development strategies necessitates multilateral cooperation in the development of renewable energies. To analyze the theme, we propose theoretical and practical approaches, correlating sustainable development theory, labor market theory and public policy theory, with practical applications in renewable energy sector strategies and policies and impact on labor markets. Keywords: renewable energies, labor markets, sustainable development, financial incentives, multilateral security